No Impaired Glucose Tolerance in Primary Insomnia Patients with Normal Results of Polysomnography - Tschepp, Johanna; Lauer, Christoph J.; Wilde-Frenz, Johanna; Pollmächer, Thomas (Frontiers in Neurology, 2017)
Background: According to recent studies sleep restriction and disruption both have a prominent negative influence on glucose metabolism. This could also be shown in sleep disorders, such as sleep apnea and the restless legs syndrome. However, similar studies regarding insomnia haven’t been that consistent, yet. Moreover, most previous studies did not include objective polysomnography (PSG) data. Methods: Patients with primary insomnia (N = 17) and healthy controls (N = 15) were investigated using psychometric tests such as the Epworth sleepiness scale and the Pittsburgh sleep quality inventory (PSQI). Two nights of full PSG were performed in all subjects and after the first PSG night subjects underwent a standard oral glucose tolerance test (OGTT). PSG-, arousal- and glucose metabolism-parameters were compared between groups. Results: Patients with insomnia were, as expected, sleepier than healthy controls and showed higher PSQI values. All PSG parameters, however, including parameters related to nocturnal arousals, did not differ between groups. Moreover, OGGT results and all other parameters of glucose tolerance were not different between insomniac patients and healthy controls. Conclusions: Our findings suggest that glucose tolerance is not impaired in patients with chronic insomnia and normal PSG-findings. Therefore, impaired glucose metabolism and diabetes related to insomnia in earlier studies might be restricted to those patients who have objectively disturbed sleep.